Genome-wide identification and in-silico characterization of phytopathogenic Taf14 gene in Fusarium oxysporum fungus, and fungicide repurposing - Md. Darun Naim; Ahmed Imtiaj; Md. Nurul Haque Mollah (PLoS ONE, 2025)
Background Phytopathogenic fungi cause global agricultural damage of around 40%, for which there is an economic loss of more than $200 billion annually. F. oxysporum is one of the top five phytopathogenic fungi worldwide, which is extremely resistant to high temperatures and antiseptic chemicals. Therefore, it is crucial to find alternative fungicides against the F. oxysporum (Fo) pathogenic fungus in order to increase crop yields. The TATA box-binding protein (TBP)-associated factor 14 (Taf14) gene in Botrytis cinerea represented by (BcTaf14) is considered as the disease-causing gene in crops. Therefore, Taf14 protein has been recommended as the potential receptor to explore effective fungicides against the corresponding diseases in crops. However, the Taf14 gene in F. oxysporum is not yet identified and characterized. Objectives The specific objectives of this study are to (i) identify and characterize F. oxysporum Taf14 (FoTaf14) gene as the Fusarium wilt disease causing gene in crops, and (ii) exploring FoTaf14 gene guided candidate fungicides against the diseases in crops. Methods This study identified FoTaf14 proteins from the whole proteome of F. oxysporum by using BcTaf14 as the query protein in BLASTP search. The integrated bioinformatics studies including phylogenetic tree, domain analysis, subcellular location, pathway terms, regulatory elements and expression analysis were performed in order to characterize FoTaf14 proteins. Then we explored FoTaf14 proteins guided candidate fungicides against the Fusarium wilt disease in crops by molecular docking analysis. Results The phylogenetic tree has shown that FoTaf14 and Taf14 from other fungal divisions are similar. The YEATS domain has been detected by domain analysis as having a direct impact on fungal pathogenicity. The subcellular location analysis revealed that all FoTaf14s are found in the nucleus and cytoplasm, which are directly related to fungal growth and pathogenicity. The gene ontology (GO) enrichment analysis has revealed some important GO-terms that are related to plant diseases. The cis-regulatory network analysis of FoTaf14 genes has shown that C-box, MYB, ABRE, SEF4, and TAAAG motifs are associated with stress, growth, and development, whereas GATA box, GT-1 motif, SEBF, HD, and W box are associated with virulence. Expression analysis has shown that FoTaf14 genes are highly expressed in the pathogenicity, growth, and development of F. oxysporum. Finally, we detected FoTaf14-protein-guided three repurposed fungicides (Oxathiapiprolin, Tolfenpyrad and Amisulbrom) for the treatment against the Fusarium wilt disease in crops by molecular docking analysis. Conclusion Therefore, the findings of this study might be useful resources for taking a proper treatment plan against Fusarium wilt disease to increase quality crop production.